2006
DOI: 10.1107/s1744309106019099
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary X-ray analysis of a Kunitz-type inhibitor, textilinin-1 fromPseudonaja textilis textilis

Abstract: Textilinin-1 (Txln-1), a Kunitz-type serine protease inhibitor, is a 59-amino-acid polypeptide isolated from the venom of the Australian Common Brown snake Pseudonaja textilis textilis. This molecule has been suggested as an alternative to aprotinin, also a Kunitz-type serine protease inhibitor, for use as an antibleeding agent in surgical procedures. Txln-1 shares only 47% amino-acid identity to aprotinin; however, six cysteine residues in the two peptides are in conserved locations. It is therefore expected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…This high number of solvent‐exposed hydrophobic residues is somewhat surprising, given that the molecule is soluble up to 40 mg·mL −1 for crystallization studies, suggesting that textilinin‐1 may form oligomers at higher concentrations. Eleven different reagent conditions yielded crystals of textilinin‐1 [15]. All of the crystals tested by X‐ray diffraction yielded a conserved set of unit cell parameters and space group, indicating consistent packing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This high number of solvent‐exposed hydrophobic residues is somewhat surprising, given that the molecule is soluble up to 40 mg·mL −1 for crystallization studies, suggesting that textilinin‐1 may form oligomers at higher concentrations. Eleven different reagent conditions yielded crystals of textilinin‐1 [15]. All of the crystals tested by X‐ray diffraction yielded a conserved set of unit cell parameters and space group, indicating consistent packing.…”
Section: Resultsmentioning
confidence: 99%
“…It was expressed in inclusion bodies as a fusion protein where a proprietary N‐terminal expression enhancer sequencer (TV) was joined to an internal tryptophan residue (W) followed by the 59 amino acid mature protein. The TVW moiety was then cleaved, and the protein was purified and crystallized as described previously [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The serine protease inhibitor, textilinin‐1, from the venom of the Australian eastern brown snake, Pseudonaja textilis is related in sequence to aprotinin and exhibits a three‐dimensional structure typical of Kunitz/BPTI‐type inhibitors (Masci et al , 2000; Filippovich et al , 2002; Millers et al , 2006). In preliminary studies, textilinin‐1 was found to strongly inhibit plasmin and trypsin (Flight et al , 2005) and to reduce blood loss in an animal model (Masci et al , 2000).…”
mentioning
confidence: 99%
“…Although the role of MMP-9 in the context of ALS is still poorly understood, it might be involved in the disruption of the neuronal extracellular matrix interaction (reviewed by [51]). MMPs have also been shown to promote the inflammatory process [52]. Kaplan et al [38] found that MMP-9 is highly expressed in the FF MNs, in contrast to the S MNs, which have undetectable MMP-9 levels ( Figure 2D).…”
Section: Mmp-9mentioning
confidence: 98%